STUDI PENGENDALIAN HAMA ULAT GRAYAK (Spodoptera frugiperda) DENGAN Beauveria bassiana PADA TANAMAN JAGUNG SECARA IN VIVO DAN IN VITRO - Lutfiyah, Nanik; Wulandari, Dwi; Sudarno, Sudarno (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
Spodoptera frugiperda is a new invasive insect in Indonesia that has become a main pest of corn plants. This pest attacks the whole living stages of corn plants from the vegetative to the generative phase and causes major damage in the vegetative phase. This research aims for the utilisation of a biological control agent, namely the entomopathogenic fungus Beauveria bassiana, to control armyworm pests (S. frugiperda) on corn plants. Application of B. bassiana was carried out on S. frugiperda with concentrations of 106, 107, 108, 109 and 1010 conidia/ml with the amount of 10 ml/treatment. The results showed that the highest mortality rate for S. frugiperda in treatment 1010 reached approximately 33% and the LC50 probit analysis had a value of 1.17 X 108. Symptoms of death in S. frugiperda caused by B. bassiana can be seen from changes in the color and shape of the insect's body, which is a sign of infection by this fungus.